PENGARUH TINGKAT KESEHATAN BANK (METODE RGEC) DAN ZAKAT PERFORMANCE TERHADAP NILAI PERUSAHAAN BANK UMUM SYARIAH - Kristanto, Eri; Faizun Khoerul Anam (JURNAL EKONOMI, 2023)
The purpose of this research is to examine the relationship between Non performing Financing (NPF), Financing to Deposit Ratio (FDR), Good Corporate Governance (GCG), Return on Assets (ROA), Capital Adequacy Ratio (CAR), and Zakat Performance Ratio (ZPR) on Firm Value Sharia Commercial Banks in 2017-2021. The population of this research is Islamic Commercial Bank with sampling technique used purposive sampling, and obtained 11 Islamic Commercial Banks. The data analysis technique used was multiple linear regression analysis. The results of this study indicate that NPF, ROA, and CAR have an effect on firm value, and FDR, GCG, and ZPR have no effect on firm value.